Molecular Weight Distributions in Ideal Polymerization Reactors. An Introductory Review - Meira, Gregorio Raul (2011)
The ultimate aim of polymerization reaction engineering is the production of polymers with tailor-made properties. An introductory review into this field is presented, with emphasis on the effects on the molar mass distribution (MMD), of the sought combination of polymerization mechanism, reactor type, and reactor control. Three ideal polymerization mechanisms are analyzed: free-radical, living anionic, and step-growth. Living anionic and step-growth polymerizations are similar in that their growing chains remain reactive while inside the reactor; and for these systems the narrowest MMDs are produced in reactors with narrow residence time distributions (RDT); i.e.: batch or continuous tubular reactors. In contrast, in conventional free-radical polymerizations, the polymer molecules grow in a fraction of a second and thereafter remain inactive while inside the reactor. In this case, the RTD does not affect the MMD, and the homogeneous continuous stirred-tank reactors provide the narrowest MMDs. Representative mathematical models of polymerization reactors are useful for: a) quantifying the interrelationships between their numerous inputs and outputs; and b) developing open- and closedloop strategies for increasing reactor productivity and product quality.